Art and architecture of Ireland : Volume V: Twentieth century - Marshall, Catherine; Marshall, Catherine; Murray, Peter; Murray, Peter; Carpenter, Andrew; Carpenter, Andrew (Roayl Irish Academy, 2015)
Introduction -- Art and artists A-Y -- The first decade of the twenty-first century -- Contemporary art glossary.